KEDUDUKAN PERATURAN DESA DALAM SISTEM PEMBENTUKAN PERATURAN PERUNDANG UNDANGAN NASIONAL - Kadek Wijayato; Lusiana Margareth Tijow; Fence M. Wantu (Prodi Ilmu Hukum, Universitas Teuku Umar, 2020)
ABSTRACTThe purpose of this study is to Analyze the position of Village Regulations after the enactment of Law Number 12 of 2011 concerning the Formation of Legislation and Know and Analyze the Urgency of Village Regulations in the Implementation of Village Government Affairs. The study uses a type of normative juridical legal research using the approach to the Act (Statute Approach), and Conceptual Approach (Conceptual Approach). The results of this study indicate: First, That the Position of the Village Regulation Post the Law No. 12 of 2011 is legally normative is not explicitly recognized in Law No. 12 of 2011 although the previous law still recognizes this point clearly in Law Number 10 of 2004 Village regulations state that Article 7 paragraph (2) letter c states